NOTES ON FOSSIL CHITONS. 5. POLYPLACOPHORA FROM THE PLIOCENE OF WESTERN LIGURIA, NORTHWEST ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
This study describes the chiton fauna (Mollusca, Polyplacophora) from deposits of the Pliocene marine sequence of Western Liguria in northwestern Italy between Genova (Genoa) and Ventimiglia. The studied fossils consist of 9,657 valves from nine sites (Bussana, Rio Sant'Antonino, Garlenda, Salea, Caranchi, Rio Torsero, Zinola, Sestri Ponente, and Borzoli; see Fig. 1) taken from the lower clayey formation named Argille di Ortovero (Ortovero Clay). From these we identified 31 species, 22 of which were already known, 5 are identified only at generic level, and four are described as new: Leptochiton josei sp. n., Ischnochiton ligusticus sp. n., Connexochiton roccai sp. n., and Lepidochitona pliocinerea sp. n. Only three species (Lepidopleurus cajetanus, Chiton corallinus and Acanthochitona fascicularis) occur in all the studied sites but, even so, it is difficult to evaluate their relative prevalence. Ch. corallinus and Lepidop. cajetanus are most common, representing 46%  and 31% respectively of the total valves found. Some species found are particularly noteworthy; Lept. alveolus previously not known as a fossil, except a dubiously identified record from the Eocene/Oligocene of Washington; Lept. bedullii and I. martinelli are known only from few Pliocene localities. Four species are described as new, and this increases the number of Mediterranean Pliocene determined species known to 37. Connexochiton roccai sp. n. represent the first report of Connexochiton as a fossil. Seventeen (55%) of the species found are still living in the Mediterranean Sea and 13 of these also occur in the eastern Atlantic. Only one species, Lept. alveolus, occurs as a living species in the Atlantic but is absent from the Mediterranean Sea. Five determined species are known only from Mediterranean Pliocene, and 12 are recorded for the first time from the Ligurian Pliocene. The analysis of the Ligurian samples suggests a shallow water depositional environment, possibly from lower infralittoral to circalittoral depth, and suggests a mixture of faunal elements from different depths and environments.
Keywords: Mollusca; Polyplacophora; Systematics; Pliocene; Liguria